2011
DOI: 10.1007/s10620-011-1995-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Clinical Features, and Prognosis of the Hepatocellular Carcinoma with Peritoneal Metastasis

Abstract: Peritoneal metastasis was not found to be an independent prognostic factor of HCC, and among HCC patients with peritoneal metastasis, those with advanced Child-Pugh class and with uncontrolled intrahepatic HCC showed poor survival. Therefore, the maintenance of favorable hepatic function and control of intrahepatic HCC should still be emphasized in HCC patients with peritoneal metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Meanwhile, the number of BM was found to be prognostic in the RTOG 9508 trial [14], and was incorporated in the original GPA score [15]. Additionally, Child Pugh Score and AFP level are important prognostic factors in HCC [26][27][28][29][30]. Therefore, we utilized these parameters to build a prognostic index specific for HCC, as they seemed to be the most clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the number of BM was found to be prognostic in the RTOG 9508 trial [14], and was incorporated in the original GPA score [15]. Additionally, Child Pugh Score and AFP level are important prognostic factors in HCC [26][27][28][29][30]. Therefore, we utilized these parameters to build a prognostic index specific for HCC, as they seemed to be the most clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Yeh and Chen observed that the rate of a spontaneous rupture was comparable between patients with peritoneal localization and patients who never recurred (25.5% and 16.4%) [8]. Kwak and colleagues, comparing the patients with peritoneal localization to a randomly matched control group, noted the same rate of needle tract injury (30.9% and 26.5%) while HCC rupture (19.1% and 4.4%) was confirmed as an independent risk factor (P = 0.008) [5]. These studies stated that a peritoneal recurrence does not necessarily appear in every patient after a spontaneous rupture of HCC, as in our experience too, but were unable to define the pathogenetic role of the percutaneous procedures.…”
Section: Discussionmentioning
confidence: 90%
“…The main pathogenetic mechanism seems to be related to the preoperative violation of the cancer integrity rather than to an intraoperative dissemination; a needle tract injury or a spontaneous rupture of the tumor was documented in 71.4% of our cases. This hypothesis is easy to demonstrate in the parietal localization with the exact coincidence of the lesion with the trajectory of the needle, while it is not proven that percutaneous procedures or HCC rupture carry a significant increase of the risk of peritoneal localization as well [5]. Yeh and Chen observed that the rate of a spontaneous rupture was comparable between patients with peritoneal localization and patients who never recurred (25.5% and 16.4%) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Since peritoneal metastasis is not a prognostic factor, with no influence on the survival time, active treatment may be meaningless. However, its treatment is generally considered to reduce the risk of complications, i.e., ileus and hydronephrosis, and improve patients' quality of life (QOL) [15]. Thus, it may be treated when liver function is relatively favorable and the intrahepatic lesion is controllable to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection has mainly been reported, and chemotherapy, TACE, PEIT, and RFA have occasionally been reported [15,16]. However, to our knowledge, there have been no reports of cases treated with B-TACE.…”
Section: Discussionmentioning
confidence: 99%